Pain Treatment On Trauma Patient In Dr.Soetomo General Hospital Emergency Room - Khoir Amaliin; Atiya Nurrahmah; Nancy Margarita Rehatta; Choesnan Effendi (Faculty of Medicine-Universitas Airlangga, 2019)
Introduction: Uncontrolled pain has many negative effects to the body. The Guideline of Pain Management has been specifically arranged, but assessment and pain treatment in the Emergency Room (ER) have not adequate yet. Integrated pain assessment before and after treatment is very important in monitoring pain management effectiveness. Objective: The aim of this study was to determine pain score of emergency patients before and after treatment. This study was also conducted to record the treatment timing that was given by the paramedics in the emergency room. Method and Material: This study was a description research with 40 trauma patients as samples in the ER at Dr. Soetomo Hospital. Patient's pain level was measured twice, before the treatment and an hour after that. The pain level was measured using Visual Analog Scale (VAS). Patients were given ketorolac 30mg intravenous as the treatment. Result and Discussion: There were2.5% of the patients VAS 1 and the other 12.5% VAS 10. An hour after treatment 20% of the ER patients were free of pain and the rest 7.5% VAS 6. The average of VAS before the treatment were 6.38 ± 2.1and an hour after later they decreased to 2.23 ± 1.7. There were only 67.5% of the ER patients that were treated in the 1st hour, 17.5% of them were treated in the 2nd hour, the other 10% were treated in the 3rd hour, and the last 5% of them were treated in the 4th hour. Conclusion:The average value of pain was decreased when one hour after administration of pain therapy by paramedics, but therapy at different times showed no difference in the level of pain reduction that can be inferred.